Study on the flowability of the green sand molding Estudo da fluxibilidade em areias de moldagem a verde - Mais V.* (2014)
© 2014 Universidade Federal do Rio de Janeiro. All rights reserved.It is described a study on the flowability of the green sand molding quantifying the influence of the degree of compaction and the properties of the mixture on the flowability. In this work two methods were chosen. One is denominated TNO which measures the difficulty of the sand grain to pass through a device’s opening and the other method is called Orlov, which quantifies the relationship between the hardness of the test piece in areas of high and low levels of compaction. The results demonstrated that the TNO method is sensitive to changes in the sand compactability, but has no correlation with the variations in the amount and type of ben-tonite. However, the Orlov method shows that a lower flowability is achieved in mixtures with a high level of compactibility, lower average size of the sand and use of greater amounts of natural sodium bentonite. Besides that, it was found that at higher levels of compactability, there is a lower flowability variation between compositions So, it can be concluded that the combined use of these two methods of flowability measurement allows to forsee the behavior of the green sand not only during the filling of the mould (TNO) but also during the compression (Orlov).